Differences in US Adults' Value of and Preferences for Sustainable Food by Race/ethnicity, Income, and Education. Issue 3 (4th May 2021) - Burt, Kate G.; Fera, Joseph; Lewin-Zwerdling, Alexandra
ABSTRACT: The purpose of this paper is to identify demographic differences in U.S. adults' value of sustainably produced foods and explore how marketing influences self-reported purchasing behavior. A secondary data analysis of questions from the 2017 International Food Information Council's Food and Health Survey was conducted. Descriptive statistics, one-way ANOVAs, and Tukey's Multiple Means Test were used to identify and compare differences in demographic groups. On average, people of color, persons with less education, and low-income earners valued sustainable food more than their peers. While some participants reported purchasing foods or beverages advertising sustainability, marketing did not influence restaurant choice.